Exploration of the breast ductal carcinoma in situ signature and its prognostic implications. (26th July 2022) - Zhang, Jiao; Lin, Hui; Hou, Lei; Xiao, Hui; Gong, Xilong; Guo, Xuhui; Cao, Xuchen; Liu, Zhenzhen
Abstract: Following the implementation of breast screening programs, the occurrence of ductal carcinoma in situ (DCIS) as an early type of neoplasia has increased. Although the prognosis is promising, 20%–50% of DCIS patients will progress to invasive ductal carcinoma (IDC) if not treated. It is essential to look for promising biomarkers for predicting DCIS prognosis. The Gene Expression Omnibus (GEO) database was used to explore the expression of genes that differed between DCIS and normal tissue in this investigation. Enrichment analysis was performed to characterize the biological role and intrinsic process pathway. The Cancer Genome Atlas Breast Cancer Dataset was used to categorize the hub genes, and the results were confirmed using the Cytoscape plugin CytoHubba and MCODE. The prognostic ability of the core gene signature was determined through time‐dependent receiver operating characteristic (ROC), Kaplan–Meier survival curve, Oncomine databases, and UALCAN databases. In addition, the prognostic value of core genes was verified in proliferation assays. We identified 217 common differentially expressed genes (DEGs) in the present study, with 101 upregulated and 138 downregulated genes. The top genes were obtained from the PPI network (protein–protein interaction). A unique six‐gene signature (containing GAPDH, CDH2, BIRC5, NEK2, IDH2, and MELK) was developed for DCIS prognostic prediction. Centered on the Cancer Genome Atlas (TCGA) cohort, the ROC curve showed strong results in prognosis prediction. The six core gene signatures is often overexpressed in DCIS, with a weak prognosis. Furthermore, when breast cancer cells are transfected with small interfering RNAs, downregulation of core gene expression substantially inhibits cell proliferation, revealing a high potential for employing core genes in DCIS prognosis. In conclusion, the current investigation verified the six core genes signatures for prospective DCIS biomarkers, which may aid clinical decision‐making for individual care. Abstract : Following the implementation of breast screening programs, the occurrence of Ductal carcinoma in situ (DCIS) as an early type of neoplasia has increased.The current investigation verified the six core genes (containing GAPDH, CDH2, BIRC5, NEK2, IDH2, and MELK) signatures for prospective DCIS biomarkers, which may aid clinical decision‐making for individual care.